Blockchain : A Potential Ingredient for Fourth Industrial Revolution - Satpathy, Diptikant (Indian Journal of Computer Science, 2018)
The business processes today are complex. With stricter compliance and policy requirements, more demanding customers, greater commercial competitions, geographically spread businesses, and vulnerable cyber security, today’s business sees a lot more challenges than ever before to track and trace each aspect of the business process. Maintaining foolproof automated systems with transparency, security, reliability, traceability has big impact on the bottom line of the organizations. A distributed ledger technology called ’Blockchain’ provides a viable solution to these problems. The technology started with its use in peer-to-peer online payment through a cryptocurrency called ’Bitcoin’, but later it has been successful in finding its application in many other fields like banking, asset management, healthcare, travel, supply chain, logistics, identity management, etc. This article discusses the high level working of blockchain technology with more focus on its applications in banking and financial sectors, supply chain management and identity management areas.Before taking a plunge into Blockchain implementation, one needs to evaluate its appropriateness. A ’Business Suitability Matrix’ has been established to help decision makers. This may assist in formulating questionnaires, and the outcome of the exercise will supplement the business decision. A separate section has been added to determine Indian scenarios and the areas where Blockchain might come handy.